Horizontal Cell Feedback to Cone Photoreceptors in Mammalian Retina: Novel Insights From the GABA-pH Hybrid Model - Barnes, Steven; Grove, James C. R.; McHugh, Cyrus F.; Hirano, Arlene A.; Brecha, Nicholas C. (Frontiers in Cellular Neuroscience, 2020)
How neurons in the eye feed signals back to photoreceptors to optimize sensitivity to patterns of light appears mediated by one or more unconventional mechanisms. Via these mechanisms, horizontal cells control synaptic gain and enhance key aspects of temporal and spatial light adaptation, including center-surround receptive field antagonism. After the transduction of light energy into an electrical signal in photoreceptors, a major task in visual processing is transmission of an optimized signal to the follower neurons in the retina. For this to happen, the release of the excitatory neurotransmitter glutamate from photoreceptors is carefully regulated via feedback from horizontal cells, which acts like a thermostat to keep synaptic transmission in an optimal range during changes in light patterns and intensities. A recently described model that casts a classical neurotransmitter system together with ion transport mechanisms to adjust the alkaline milieu outside the synapse, is emphasized here. We review the new evidence showing how this novel inter-neuronal messaging system carries the feedback inhibition using two separate, but interwoven, regulated systems. It may be the complex interplay between these two signaling modalities, creating synaptic modulation-at-a-distance, that has made its definition difficult. The foundations of our understanding of the feedback mechanism from horizontal cells to photoreceptors have been long established: Horizontal cells have broad receptive fields, suitable for providing surround inhibition, their membrane potential regulates inhibition of photoreceptor voltage-gated calcium channels, and strong artificial pH buffering eliminates this action. This report compares and contrasts models of how these foundations are linked, focusing on a recent report of a novel action of GABA in mammals that shows tonic horizontal cell release of GABA activating chloride and bicarbonate permeable GABA autoreceptors. The membrane potential of horizontal cells provides the driving force for GABAR-mediated bicarbonate efflux, alkalinizing the cleft when horizontal cells are hyperpolarized by light or adding to their depolarization cells in darkness by contributing to cleft acidification via NHE-mediated proton efflux. This model reverses interpretations of earlier studies that were considered to rule out a role for GABA in feedback to cones.